Estudo teórico e experimental da segurança de filtros de barragens de terra à erosão interna - Araujo, Antonio Anderson Fontenele (2019)
Internal erosion is a process of removing and carrying soil particles due to the action of the water flow. Such phenomenon represents one of the main causes of dam ruptures worldwide, and is normally associated with the absence or failure of dimensioning of the internal drainage system. Granular filters are structures used to control and stabilize the loss of grains susceptible to internal erosion, capturing them between your constrictions. For that, it is necessary that the filter presents an adequate granulometry to guarantee this efficient filtration process. This problem becomes more relevant in the semiarid region of northeastern Brazil, where cyclical processes of reservoir filling and drying help trigger internal erosion. Criteria empirical tests were developed for filter designs, based on particle distribution, that consist in relating characteristic diameters of the filter grains with soil grains that if you want to protect. More recent studies have presented a new analytical approach related to determining the distribution of the internal constraints of the granular filter, which have proved to be more realistic in assessing the filtering behavior of these structures. It is Therefore, this dissertation aims to present a methodological study of these granular filters on earth dams. The methodology consists of developing two experimental earth dam models, dimensioned according to the constriction distribution, with the experimental results compared with the criteria empirical particle distribution. Finally, a methodology for the evaluation of internal drainage systems, based on the constriction distribution approach and applied in two dams in the state of Ceará, the Benguê and Itaúna dams. The results revealed that the approach to criteria based on the distribution of internal filter constrictions granular is more realistic, adequate and safe to identify the efficiency of granulometries regarding the ability to interrupt internal erosion processes.